2015
DOI: 10.1108/bfj-07-2014-0252
|View full text |Cite
|
Sign up to set email alerts
|

Is there an expectation gap? Consumers’ expectations towards organic

Abstract: Purpose – While the European organic regulation exists since more than 20 years consumers still do not seem to know what to expect from European Union (EU) labelled organic food. The purpose of this paper is to examine consumer expectations towards organic food in mature and emerging EU organic food markets. Design/methodology/approach – Online consumer survey data (n=1,180; 2011) from Germany, the UK, Spain, and the Czech Republic are u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 32 publications
3
32
0
Order By: Relevance
“…(Spanish stakeholder). This identification of the risk of consumer backlash associated with asking consumers to pay more for "improved" animal health when they already expect the delivery of good animal health and welfare when buying "normal" organic products replicates the findings of previous studies [36,37].…”
Section: Legislation and Market Differentiationsupporting
confidence: 78%
“…(Spanish stakeholder). This identification of the risk of consumer backlash associated with asking consumers to pay more for "improved" animal health when they already expect the delivery of good animal health and welfare when buying "normal" organic products replicates the findings of previous studies [36,37].…”
Section: Legislation and Market Differentiationsupporting
confidence: 78%
“…This is confirmed by most of the studies conducted in different markets that suggest that the most important motives for buying organic food are related to consumer perception of these products as healthy, tasty, safe, and of high nutritional value [9,10,20]. Additionally, consumers believe that organic production ensures protection of the environment, animal welfare, and preservation of natural resources [9][10][11]13,20,28]. Additionally, it should be pointed out that health and environmental concerns are far more important than other reasons, as well as the fact that the relative importance of each of these reasons did not significantly change over time [29].…”
Section: Theoretical Backgroundmentioning
confidence: 88%
“…These results are somewhat surprising, considering the fact that earlier studies confirmed the specificities of the organic production system and objective features of organic food products (such as their nutritive value, health benefits, environmental benefits, etc.) as the main motives for buying these products [9][10][11]13,20,28,29]. However, the explanation could be found in the analysis of the significance of the factors that influence consumer perception of organic food products.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is widespread consensus that environmentally and socially sustainable food production is needed to tackle future challenges, such as the degradation of natural resources, the loss of biodiversity and the on-going rural depopulation (Meyer-Höfer, Nitzko & Spiller 2015). Thus, organic food production systems are seen as one possible solution to these problems (Padel & Foster, 2005;Thøgersen, 2009).…”
Section: Introductionmentioning
confidence: 99%